GABAergic regulation of the HPA and HPG axes and the impact of stress on reproductive function - Melón, Laverne Camille (J Steroid Biochem Mol Biol, 2015)
The hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axes are regulated by GABAergic signaling at the level of corticotropin-releasing hormone (CRH) and gonadotropin-releasing hormone (GnRH) neurons, respectively. Under basal conditions, activity of CRH and GnRH neurons are controlled in part by both phasic and tonic GABAergic inhibition, mediated by synaptic and extrasynaptic GABA(A) receptors (GABA(A)Rs), respectively. For CRH neurons, this tonic GABAergic inhibition is mediated by extrasynaptic, δ subunit-containing GABA(A)Rs. Similarly, a THIP-sensitive tonic GABAergic current has been shown to regulate GnRH neurons, suggesting a role for δ subunit-containing GABA(A)Rs; however, this remains to be explicitly demonstrated. GABA(A)Rs incorporating the δ subunit confer neurosteroid sensitivity, suggesting a potential role for neurosteroid modulation in the regulation of the HPA and HPG axes. Thus, stress-derived neurosteroids may contribute to the impact of stress on reproductive function. Interestingly, excitatory actions of GABA have been demonstrated in both CRH neurons at the apex of control of the HPA axis and in GnRH neurons which mediate the HPG axis, adding to the complexity for the role of GABAergic signaling in the regulation of these systems. Here we review the effects that stress has on GnRH neurons and HPG axis function alongside evidence supporting GABA(A)Rs as a major interface between the stress and reproductive axes.